Effects of the 5:2 intermittent fasting diet on non-alcoholic fatty liver disease: A randomized controlled trial - Kord Varkaneh, Hamed; Salehi sahlabadi, Ammar; Găman, Mihnea-Alexandru; Rajabnia, Mohsen; Sedanur Macit-Çelebi, Melahat; Santos, Heitor O.; Hekmatdoost, Azita (Frontiers in Nutrition, 2022)
Background and Aims: Dietary regimens are crucial in the management of nonalcoholic fatty liver disease (NAFLD). The effects of intermittent fasting (IF) have gained attention in this regard, but further research is warranted. Thus, we aimed to ascertain the overall effects of the 5:2 IF diet (5 days a week of normal food intake and 2 consecutive fasting days) in patients with NAFLD compared to a control group (usual diet). Methods and Results: A 12-week randomized controlled trial was performed to evaluate the effects of the 5:2 IF diet on anthropometric indices, body composition, liver indices, serum lipids, glucose metabolism, and inflammatory markers in patients with NAFLD. The IF group (n = 21) decreased body weight (86.65±12.57 to 82.94±11.60 kg), body mass index (30.42±2.27 to 29.13±1.95 kg/m2), waist circumference (103.52±6.42 to 100.52±5.64 cm), fat mass (26.64±5.43 to 23.85±5.85 kg), fibrosis (6.97±1.94 to 5.58±1.07 kPa), steatosis scores/CAP (313.09±25.45 to 289.95±22.36 dB/m), alanine aminotransferase (41.42±20.98 to 28.38±15.21 U/L), aspartate aminotransferase (34.19±10.88 to 25.95±7.26 U/L), triglycerides (171.23±39.88 to 128.04±34.88 mg/dL), high-sensitivity C-reactive protein (2.95±0.62 to 2.40±0.64 mg/L), and cytokeratin-18 (1.32±0.06 to 1.19±0.05 ng/mL) values compared to baseline and end of control group (n = 23)—p-values ≤ 0.05 were considered as significant. However, the intervention did not change the levels of high-density lipoprotein cholesterol, total cholesterol, low-density lipoprotein cholesterol, fasting blood sugar, insulin, HOMA-IR, and total antioxidant capacity. Conclusions: Adhering to the 5:2 IF diet can reduce weight loss and related parameters (fat mass and anthropometric indicators of obesity), as well as hepatic steatosis, liver enzymes, triglycerides, and inflammatory biomarkers in patients with NAFLD.